Climate station data from the Sheldrake river region in Nunavik, Quebec, Canada : Données des stations climatiques de la région de la rivière Sheldrake au Nunavik, Québec, Canada - Centre D'études Nordiques (Nordicana D, 2020)
Data are from the Sheldrake river region in Nunavik, Quebec, Canada. It contains data from air and ground temperatures. The available datasets cover the period from 1986-2019. For each site, the number of measured variables differs. For ground temperature, the depth ranges are as follows: Rivière Sheldrake, Site A (SHELDRA) : 0-200 cm. Rivière Sheldrake, Site B (SHELDRB) : 0-292 cm. Data are available as: (1) recorded data; (2) daily averages; (3) monthly averages; and (4) yearly averages. : Les données proviennent de la région de la rivière Sheldrake au Nunavik, Québec, Canada. On y retrouve des données de température de l'air et du sol. La période couverte par les données est 1986-2019. Pour chaque site, le nombre de variables mesurées varie. Pour les données de température de sol, les intervalles de profondeur sont: Rivière Sheldrake, Site A (SHELDRA) : 0-200 cm. Rivière Sheldrake, Site B (SHELDRB) : 0-292 cm. Les données sont disponibles en quatre formats: (1) données enregistrées; (2) la moyennne journalière; (3) la moyenne mensuelle et (4) la moyenne annuelle.